A pathway to produce strong and tough martensitic stainless steels resistance spot welds. (3rd April 2019) - Aghajani, H.; Pouranvari, M.
ABSTRACT: Martensitic stainless steel (MSS) resistance spot welds are prone to quasi-cleavage interfacial failure with very low energy absorption capability due to formation of hard and brittle carbon and chromium rich martensite in the fusion zone (FZ). In this work, a new pathway is proposed to enhance strength/toughness of the MSS resistance spot welds based on modification of the FZ composition/microstructure via introducing a nickel interlayer. This altered the FZ microstructure from dual phase microstructure of martensite and δ-ferrite to austenitic microstructure with finely dispersed ultra-fine chromium rich carbides. Formation of a tough predominately austenitic microstructure in the FZ enabled achieving a pullout failure with an unprecedented level of energy absorption.